Reference ranges and determinants of tricuspid regurgitation velocity in healthy adults assessed by two-dimensional Doppler-echocardiography - Marra, Alberto M.; Eichstaedt, Christina; Benjamin, Nicola; Grünig, Ekkehard (Respiration, 2018)
Background: Tricuspid regurgitation velocity (TRV) is the most widely used parameter by transthoracic echocardiography (TTE) in the evaluation of patients with suspected pulmonary hypertension (PH). Objectives: To explore the physiologic range of TRV in healthy adults and to investigate its clinical determinants. Methods: In the first part of the study, 614 healthy individuals (age 45.7± 14.7 years, 60.26% women) were prospectively assessed by TTE. In the second part, a pooled meta-analysis of 16 already published studies with TRV values in healthy subjects (n = 981) was performed. Statistical analysis included the calculation of 95% quantiles for defining reference ranges. Results: In the prospectively enrolled cohort, mean TRV was 2.01 ± 0.29 m/s (5-95% CI 1.987-2.033 m/s). It was significantly but weakly positively correlated with age, body mass index, systolic blood pressure, diastolic blood pressure, left atrial volume and negative with mitral inflow E/A ratio. No significant differences were found between males and females. The prospectively enrolled data revealed similar values to the literature-based datasets resulting in a mean TRV of 1.96 m/s (95% CI 1.91-2.02 m/s) and a 95% quantile of 2.55 m/s.Conclusions: To the best of our knowledge, this is the largest dataset to describe reference ranges of TRV and their clinical determinants in healthy adults years. The determined cut-off value of 2.55 m/s of this study has to be confirmed in specific pathologies such as patients at risk of PH.
Gesehen am 14.10.2019